FILTER BANK MULTICARRIER (FBMC) UNTUK 5G - Gradiyanto Jason; Theresia Ghozali; Kumala Indriati (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2020)
Currently, technology in the telecommunications sector is developing rapidly.Telecommunication users need fast communication technology with wider bandwidth. Therefore, FBMC / OQAM was developed, which is a modulation candidate technology to be used in 5G. FBMC / OQAM is a development of OFDM which is modified by using filters to reduce noise. OFDM uses a multiplexing technique that divides bandwidth into several sub-carrier frequencies. But OFDM has a weakness, because it requires a Cyclic Prefix (CP) to overcome Intersymbol nterference (ISI) and Intercarrier Interference (ICI). With FMBC, the increased bandwidth due to the Cyclic prefix can be reduced. The filter used is based on the Physical layer for dynamic spectrum access and cognitive radio (PHYDYAS).The results achievedin this study were that FMBC was succesfully and the data sent was the same as the data received